A Mixed Method Analysis of the Cognitive Levels Manifested in English Quarterly Tests: Basis for Enhancing Teacher Assessment Practices in Asipulo District - Gallangi , Melanie; Bumidang, Marites (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the cognitive levels manifested in English summative tests administered in the Asipulo District and served as a basis for enhancing teachers’ assessment practices. Using a mixed-method research design, the study combined quantitative content analysis of test items and qualitative data gathered from teacher interviews to provide a comprehensive understanding of current assessment practices. The quantitative phase involved analyzing English summative test items using Bloom’s Taxonomy of cognitive domains to determine the distribution of lower-order and higher-order thinking skills. Results revealed that the overall cognitive level of the summative tests falls under lower-order thinking skills, indicating that most test items emphasize remembering, understanding, and basic comprehension rather than analysis, evaluation, and creation. The qualitative findings further revealed that while teachers recognize the importance of incorporating Higher-Order Thinking Skills (HOTS) in assessments, they encounter several challenges in crafting such test items. These challenges include limited time for test construction, difficulty in designing context-based and analytical questions, and the need for additional training and resources related to HOTS-based assessment. Based on these findings, the study highlights the need to strengthen teachers’ assessment practices by promoting professional development programs focused on the development of HOTS-oriented test items. Enhancing teachers’ competencies in assessment design can help ensure that English summative tests effectively measure deeper learning and critical thinking among students. The results of the study may serve as a basis for improving assessment strategies and supporting teachers in developing more cognitively demanding evaluation tools in the Asipulo District.
Keywords: : Higher-order thinking skills, English summative tests, cognitive levels, HOTS, LOTS, assessment practices, teacher assessment literacy, Asipulo District